Study of maternal and fetal outcome in HIV positive women on HAART therapy in a tertiary hospital - Shankar, Priya; J., Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: India has the third largest population of HIV. Moving from single dose nevirapine in labor to use of HAART treatment for all pregnant women and the outcome of the same was the subject of present study. Methods: Retrospective study of HIV positive pregnant women on HAART treatment admitted in labor room at Karnataka institute of medical sciences from June 2015 to December 2016. A retrospective analytical study of 93 women with HIV positive status on HAART therapy admitted in labor at KIMS was done by collecting data from case records. Baby follow up details were collected from ART center, KIMS. Results: Parameters studied were maternal and fetal outcomes. Maternal outcome in terms of mode of delivery, morbidity and mortality and fetal outcomes in terms of APGAR at birth, weight of the baby, NICU admission, incidence of meconium, still birth and intrauterine fetal demise, follow up of the babies at 6 weeks, 6 Months and 18 Months for seropositivity. Conclusions: HAART in pregnant women significantly improved the maternal and fetal outcomes.